Rethinking leadership in extended education: how collaborative development drives organizational quality - Kielblock, Stephan (Frontiers in Education, 2025)
Effective school leadership significantly impacts student learning outcomes and equitable educational opportunities. However, the increasing complexity of educational environments—marked by expanded learning spaces and diverse institutional involvement—presents new challenges. This study investigates leadership approaches within Germany’s extended education system, using all-day schooling as a case study. Data were collected from 1,355 school leaders across primary and secondary schools via a standardized online questionnaire. Structural equation modeling was employed to explore the effects of shared leadership responsibility and collaborative school development on key organizational quality indicators: designated collaboration time, breadth of extracurricular aims, and curricular-extracurricular synergy. The findings highlight that collaborative school development, rather than shared leadership responsibility, is the primary driver of organizational quality across all measured indicators. Shared leadership responsibility, while less impactful overall, contributes to the allocation of staff collaboration time, a crucial factor for teamwork and integration. These results underscore the importance of fostering collaborative practices within leadership frameworks to enhance educational quality in extended education contexts. This study provides insights into broader leadership strategies that prioritize collaboration as a cornerstone of innovation and progress in extended education.